A Study of Parameter Setting for Signal Warning Detector (SWAD) - Sarif, Muhammad Azim Farhi; Hassan, Suhaimi (Research Progress in Mechanical and Manufacturing Engineering, 2022)
An employee for road maintenance is a person who ensures safe, clean and accessible roads and highways. They do a lot of works that can expose these workers to the risky conditions as nowadays there were numerous accident involve the highway workers on the road. As the road accident among the highway workers become a concern, Signal Warning Detector (SWAD) was developed to be a part of safety system to give early warning to the highway workers. The objectives of this study are to develop a stable SWAD consist of uRAD sensor and to determine the best parameter setting of the SWAD. The method used for this study was by doing the field test of the SWAD. The test was done at Padang Kawad, UTHM by set up the SWAD at the left lane divided by cones with interval of 10 meter until 100 meter. Then, a car was used to test the ability of the SWAD by drove approaching the SWAD and the data collected when the output of the SWAD activated. According to the result obtained, the uRAD sensor in the SWAD able to detect the presence of the vehicle at a distance that can be consider safe to give the early warning to the PLUS workers so that they can react if a vehicle entering the emergency lane.